PEMBUATAN MESIN PELELEH COKLAT DENGAN MEMODIFIKASI PRODUK AKEBONNO MODEL: 9818 MENGGUNAKAN REVERSE ENGINEERING & ENGINEERING DESIGN (VDI 2221) - Wongso, Sariputra; Daywin, Frans Jusuf; Gozali, Lina (Universitas Tarumanagara, 2023)
Indonesia is one of the top chocolate producers in the world. Indonesia is capable of producing primary and secondary products of processed chocolate. The primary product of processed chocolate is cacao seeds, while the secondary products as nata and raw material for composts. Along with the growth of Indonesia’s chocolate planting area, Indonesia’s production activities need to develop as well to optimize Indonesia’s process production. One of the machines that is used on processing primary product of chocolate is chocolate melting machine. Chocolate melting machine function to regulate chocolate paste temperature, that mixed fat in chocolate optimally. Chocolate melting machine also needs to keep temperature down for chocolate’s fat shrinkage, and to regulate chocolate’s temperature for pouring into mold. Akebonno model: 9818 is a product that able to keeps temperature on chocolate paste to mix fat and chocolate. This product can also keep chocolate’s temperature for chocolate’s fat shrinkage. With reverse engineering applied, this research can describe the function of each component on the machine, and develop a product that will further easier production process.